Ancient scholarship on Aristophanes - Willi, A (Wiley-Blackwell, 2024)
This chapter examines ancient Greek scholarship on Aristophanes. It surveys the primary authors and categories of such scholarship, including Aristotle, the scholia, the Atticists, and other late antique and Byzantine encyclopedists and grammarians. After an extensive historical sketch of the relevant material, it presents a synchronic analysis of prominent themes and topics in pre-modern comic scholarship.